2018
DOI: 10.1061/(asce)gt.1943-5606.0001891
|View full text |Cite
|
Sign up to set email alerts
|

Compression and Strength Characteristics of Two Silts of Low and High Plasticity

Abstract: The potential for enhanced strength or stiffness arising from the microstructure of natural silty soils compared to their reconstituted state is examined using the framework proposed by Burland for clays, to assess to what extent it can be used for silts. A detailed study performed on two clayey silts of low and high plasticity respectively, in their intact and reconstituted state, is used to illustrate the different response of the silts compared to clays in terms of compressibility and strength e.g. multipli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…As the confining pressure increases, the stress-strain curves of the two converge, and the effect of structural characteristics on the strength of loess is weakened. Georgiannou et al showed that the response of remodeled soil can be used as a reference for identifying the effect of structural properties on the compressibility and strength of undisturbed soil [ 24 ]. It can be seen that the mechanical properties of soil are closely related to its structural changes, and it is imperative to study the structural properties of loess.…”
Section: Introductionmentioning
confidence: 99%
“…As the confining pressure increases, the stress-strain curves of the two converge, and the effect of structural characteristics on the strength of loess is weakened. Georgiannou et al showed that the response of remodeled soil can be used as a reference for identifying the effect of structural properties on the compressibility and strength of undisturbed soil [ 24 ]. It can be seen that the mechanical properties of soil are closely related to its structural changes, and it is imperative to study the structural properties of loess.…”
Section: Introductionmentioning
confidence: 99%